2017
DOI: 10.4103/0259-1162.206853
|View full text |Cite
|
Sign up to set email alerts
|

Nonopioid (Dexmedetomidine, Dexamethasone, Magnesium) adjuvant to ropivacaine caudal anesthesia in pediatric patients undergoing infraumbilical surgeries: A comparative study

Abstract: Background:Desirable adjuvants to caudal ropivacaine are the one which prolongs analgesia and free of side effects. We compared nonopioid drugs dexmedetomidine, dexamethasone, and magnesium as adjuvants to ropivacaine caudal analgesia in pediatric patients undergoing infraumbilical surgeries.Materials and Methods:This study was done on 128 pediatric patients (3–12-year olds) undergoing infraumbilical surgeries; they were randomly allocated to four groups to receive normal saline, dexmedetomidine 1 μg/kg, dexam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…All studies included patients with an American Society of Anesthesiologists physical status of I or II. In the trial by Sridhar et al [ 16 ], the participants underwent infraumbilical surgery with no more details given, while in the rest of the trials, the patients underwent surgery of the male genitalia or the groin. In all trials, participants were predominantly male.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies included patients with an American Society of Anesthesiologists physical status of I or II. In the trial by Sridhar et al [ 16 ], the participants underwent infraumbilical surgery with no more details given, while in the rest of the trials, the patients underwent surgery of the male genitalia or the groin. In all trials, participants were predominantly male.…”
Section: Resultsmentioning
confidence: 99%
“…Askar et al reported that FLACC scores were better in the magnesium group at 2, 4, and 6 h after surgery than in the control group. [ 17 ] Sridhar et al reported that the Modified Objective Pain Score was significantly better at 6 h and 12 h after surgery in the magnesium group [ 16 ]. The pain scores were similar in the other two trials.…”
Section: Pain Scorementioning
confidence: 99%
See 3 more Smart Citations